Evaluation of functional outcomes following anterior cruciate ligament augmentation - Thundathil, Sreejith; Iqbal, Eizaz; Suresh, Nihal; Das, Sneha; Ismail, Hamna; Karimban, Aslah; Rasheed, Zaeem (International Journal of Research in Orthopaedics, 2026)
Background: The anterior cruciate ligament (ACL) is the ligament of the knee, which plays a role for maintaining joint stability, which when damaged causes instability in movements. While ACL reconstruction aims to repair the torn ligament, patients are not confident in the stability and function of their knees. ACL augmentation preserves the neurovascular bundle, which can retain the proprioception and joint sensations. The aim of the study was to evaluate the functional outcome of patients post ACL Augmentation surgery. Methods: This study was a cross-sectional, survey-based, observational one which included 38 patients who underwent arthroscopic ACL augmentation involving the anteromedial (AM) or posterolateral (PL) bundle. Knee function was assessed using the Lysholm and IKDC scoring systems during follow-up. Results: Among 38 patients 25 were male and 13 were female with the most common age group being 31 to 40 years followed by 21 to 30 years. In terms of function, both scoring systems showed statistically significant improvement post-surgery. Conclusions: ACL augmentation has significant positive functional outcomes as demonstrated by remarkable increases in the Lysholm and IKDC scores. These findings support the theoretical benefit that preserving the intact neurovascular fibers is beneficial and augmentation is a successful method for treating partial ACL tears.